Comportamiento agronómico de híbridos de maíz en dos municipios de Veracruz, México. - Tosquy-Valle, Oscar Hugo (2005)
Agronomic performance of corn hybrids in two municipalities of Veracruz, Mexico. Corn productivity under rainfed, in Tlalixcoyan and San Andrés Tuxtla, Veracruz, Mexico is limited by low yield and disease susceptibility y advanced generations of improved varieties. With the purpose of assessing the agronomic behavior of corn hybrids during the 2002 rainy season, 23 experimental hybrids and the regional varieties H-520 and H-519C were evaluated in the localities indicated above; a 5 x 5 lattice statistical design with three replications was utilized. The variables that were measured in both localities were: days to male flowering, plant and ear height, percentage of rotten ears and grain yield, while the severity to stunting was only measured in Tlalixcoyan. The individual analyses showed significance for all the variables in both localities. CMS 993013 and CMS 993015 were the most productive hybrids with grain yields of 9.57 and 8.44 t/ha, respectively, 3.32 t/ha higher than the regional varieties. They had good agronomic behavior and were tolerant to the stunting in Tlalixcoyan, CMS 973023 with 7.52 t/ha and CMS 993033 with 7.29 t/ha were the best hybrids in San Andres Tuxtla; they had an average yield 3.16 t/ha higher than the regional varieties, presented low percentages of ear rotting and their plant height and life cycle were intermediate. The highest average yields troughout localities were obtained with CMS 973023, CMS 993013 and CMS 993033, which yields were higher than 7.50 t/ha, although only the first and the last one maintained high yield in both localities. The correlation showed that stunting in Tlalixcoyan and ear rotting in San Andrés Tuxtla significantly affected grain yield.